El Niño-Southern Oscillation (ENSO) Signal in an Ice Core from Huascarán, Peru, 1994-2019 - Bayless, Laurel (The Ohio State University, 2021)
A presentation of this thesis won 3rd place in the Environment and Climate Sciences category at the 2021 Denman Research Festival. This project investigates potential signatures of El Niño-Southern Oscillation (ENSO) as identified from analyses of an ice core from the col of Huascarán glacier (9.1⁰S, 77.6⁰W, 6050 m asl) in northern Peru. A reliable chemical signature of ENSO preserved in the ice offers the potential to extend the ENSO history beyond modern climatological observations. Knowledge of the history of ENSO will advance our understanding of modern climatological variability in ENSO patterns and may provide insight into how ENSO may evolve in a warmer climate. Two ice cores were recovered to bedrock in 2019 on the col of Huascarán glacier in the Peruvian Andes by a team from the Byrd Polar and Climate Research Center. Variations in the annual concentrations of F-, Cl-, SO42-, NO3-, Na+, NH4+, K+, Mg2+, Ca2+, MSA (methane sulfonic acid, CH3SO3-), δ18O, δD, and net accumulation were compared for El Niño events (1997-1998, 2009-2010, and 2015-2016), La Niña events (1998-2000, 2007-2008, and 2010-2011), and the other more neutral years from 1994 to 2019 measured in the same core. Annual values of the chemical markers and net accumulation were compared with standardized indices of sea surface temperatures (SSTs) in specific regions of the Pacific and Pacific Oceans (e.g., NIÑO4, NIÑO3.4, and AMO, the Atlantic Multidecadal Oscillation). Modeled upper tropospheric temperatures at Huascarán were compared with both Pacific SSTs and the Huascarán records to explore possible mechanisms for the connections identified. Consistent with previous research, the strongest relationship exists for isotopic variations (between 18O and 16O and between 2H and 1H) and NIÑO4 SSTs (r=0.68 and r=0.67 for δ18O and δD, respectively). Other ENSO indices also were significantly positively correlated with isotopic values. A significant negative correlation exists between NIÑO4 SSTs and net accumulation (r =-0.451, p<0.05). T-tests indicate depletion of sulfate during El Niño events. A significant relationship (r=0.571, p<0.05) exists between the AMO and dust concentration. A possible mechanism for this connection is suggested by the very strong correlation between upper tropospheric temperatures (200 and 500 mb) and central Pacific SSTs. Central Pacific SSTs could influence the upper tropospheric temperatures at Huascarán, which could in turn influence the isotopic ratios in the ice at Huascarán. The ice core drilling and analyses were supported by NSF project 1805819. No embargo Academic Major: Geography